Monitoring fatigue and recovery by use of the Lamberts and Lambert submaximal cycling test - Hammes, D.; Skorski, S.; Schwindling, S.; Meyer, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Monitoring of performance, fatigue and recovery is considered as crucial to prevent non-functional overreaching and overtraining. The Lamberts and Lambert Submaximal Cycle Test (LSCT) is a novel test which was designed to monitor performance as well as fatigue and recovery in cyclists (Lamberts et al., 2011). Few studies have shown the ability of the LSCT to predict performance; however, there is a lack of studies in which accumulated fatigue was systematically induced. The aim of this study was to determine the effect of an intensive training phase and a following recovery period on the LSCT results. Methods: 23 trained male cyclists (31±9 years; 9900±4832 annual km) completed an 11-days training camp. The LSCT was conducted on a cycle ergometer (Cyclus 2) at day 1 (d1), before the onset of training, day 8 (d8) and day 11 (d11). After d1, a 6-day training period consisting of two cycling sessions per day was performed: in the morning: 1h at 95% of individual anaerobic threshold (IAT) or 3x5x30s sprints; in the afternoon: 3h at 80% IAT. Between d8 and d11, a 72h recovery period without training was realized. For the LSCT, participants were asked to cycle at three stages with fixed predetermined heart rates of 6 min at 60%, 6 min at 80% and 3 min at 90% of maximum heart rate (HRmax). During the stages, power output and rating of perceived exertion (RPE) were determined. Immediately after stage 3, the participants had to stop cycling and sit straight for 90 s to measure heart rate recovery (HRR). Results: Total session RPE (Foster et al., 2001) of the 6-day training period was 11690±2618. Power output for the stages changed between testing days (d1, d8, d11): stage 1: 102±35W, 118±33W, 120±35W (p=0,001); stage 2: 205±37W, 244±33W, 231±39W (p<0,001); stage 3: 267±49W, 286±36W, 280±37W (p=0,08). The same applies for RPE at stages 2 (3,7±0,9; 5,2±1,9; 3,8±1,1; (p<0,001) and 3 (5,6±0,9; 8,1±1,7; 6,3±1,7 (p<0,001)), whereas stage 1 remained unchanged (p=0,71). At d8 we observed that most of the athletes were not able to reach the target HR of stage 3 (n=15 out of 23). HRR showed no difference between tests (p=0,20). Discussion: The main finding of the study was that the LSCT can be used for monitoring fatigue and recovery in cyclists, as power output and RPE measured during submaximal stages based on HRmax were responsive to a fatiguing training and a following recovery period. However, HRR as a part of the LSCT did not show its utility as a marker of fatigue. Changes in workload and RPE corresponding to fixed submaximal HR are presumably due to effects of training load on cardiac autonomic activity.